Precise measurement of energies in 115Sn following the (n, γ) reaction - Urban, W.; Köster, U.; Jentschel, M.; Mutti, P.; Märkisch, Bastian; Rząca-Urban, T.; Bernards, Ch.; Fransen, Ch.; Jolie, J.; Thomas, T.; Simpson, G. S. (Physical review. C, Nuclear physics, 2016)
The first measurement of γ rays from the 114Sn(n,γ) reaction using cold neutrons, performed with an array of Ge detectors at the PF1B facility of the Institute Laue-Langevin in Grenoble, has provided the most accurate energy, Qβ=173(12) eV, of β− decay of the 115In ground state to the first excited state in 115Sn. This is the lowest of all such energies in the known nuclear landscape. The accuracy of the neutron binding energy of 115Sn and the mass of 114Sn have been improved.
Die 115 im Titel ist hochgestellt, gamma ist als griechischer Buchstabe dargestellt
Gesehen am 29.05.2020